BUDDHIST EDUCATION SYSTEM IN ANCIENT INDIA: AN INTRODUCTION - Pintu Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Education in ancient India touched a high level of development both in the sphere of organised and unorganized sectors and provided water and manure to Indian knowledge traditions. Now ancient education system and culture is not only history but also became a reality through the adoption of its several features in National Education Policy 2020. The present essay will introduce the Buddhist education system and associated institutional culture in detail with its important features. It should be noted with emphasis that the structure of ancient Indian education primarily materialized from religions like Brāhmaṇism, Jainism and Buddhism. Especially in the process of consolidation and expansion religions like Brāhmaṇism and Buddhism played vital roles in creating, preserving and transmitting Indian knowledge through its gurukulas and mahāvihāras. The chapter will focus on Buddhist monasteries, which represent the beginning of the second stage of growth i.e. organised instruction in ancient India. Ancient Indian monasteries like Nālandā, Vikramaśīlā, Valabhī and Odantapurī were both a centre of Buddhism and the world-famous institution of learning. The organised and unorganised stages went on parallel and interacted with each other. Altogether the pre-modern Indian education became the world’s pinnacle with creation, preservation and transmission of the latest knowledge in both secular and religious subjects.